Raveling the brain : toward a transdisciplinary neurorhetoric - Jack, Jordynn, 1977- (New directions in rhetoric and materiality., 2019)
"Examines the role of the humanities, particularly rhetoric, in neuroscience, showing how the brain is enmeshed in the body, in culture, and in discourse. Uses examples of studies on sex and gender, political orientation, and affect to argue for a rhetoric-based approach to neuroscience"--